The technology education curriculum in New Zealand: Implications for initial teacher education programmes - Reinsfield, Elizabeth (Australasian Journal of Technology Education, 2022)
The changes to the New Zealand Curriculum in technology education has implications for the nature of Initial Teacher Education (ITE) programmes, which prepare secondary technology teachers for the profession. This article reports on a secondary technology student teacher’s evolving understanding during her one-year ITE programme. Data were collected of her learning process, to extrapolate findings about curriculum meaning-making and knowledge for practice. The student’s learning journey reflected similar challenges to existing secondary technology educators in the profession, and imply a need to support the development of resilience and self-regulatory practices, to enable a transformation of understandings. Recommendations advocate for the use of strategies which foster positive learning environments and expose student teachers to anchored approaches to learning. Such strategies are promoted as a means for student teachers to navigate disparities between what practicing teachers may value and what academic researchers assert is important to enable a future-focused approach for education.